Epidemiological findings of ocular dermoid in dogs and cats: 50 cases (2007-2024) - João A.T. Pigatto; Luísa S. Cargnin; Alana P. Melo; Rafaella S. Rocha; Maria E.M. Franceschini; Natália P. Méndez; Maiara P. Seibel; Marina A. Martins; Alessandra F. Silva; Luciana Sonne (Pesquisa Veterinária Brasileira)
ABSTRACT: A dermoid is a tissue that resembles normal skin in a non-typical anatomical region. Dermoids can be found in various organs and affect ocular structures in the growth of normal tissue in a non-typical anatomical region. The aim of this study was to describe clinical signs, location, histopathologic findings and breed, age, and sex profile of dogs and cats diagnosed with ocular dermoids in the specialized Veterinary Ophthalmology Service of the Federal University of Rio Grande do Sul. Medical records of dogs and cats diagnosed with ocular dermoids from January 2007 to January 2024 were evaluated. Data regarding age, breed, gender, the affected eye and the location of the dermoid were recorded. In total, 53 eyes of 49 dogs affected with dermoid were included in the study. Of these dogs, 29 (59.18%) were male and 20 (40.82%) were female. Of the total number of dermoids diagnosed, 18 (33.96%) were located in the limbal region, 11 (20.75%) in the corneal region, 11 (20.75%) in the eyelid region, five (9.43%) in the bulbar conjunctiva region, five (9.43%) in the conjunctival and palpebral regions, two (3.77%) in the third eyelid and one (1.89%) in the limbal and corneal regions. The average age of the patients at the time of dermoid diagnosis was 1.17 years. In total, 12 dog breeds were represented, including Shih-Tzu, Labrador, Dachshund, French Bulldog, Pug, Rottweiler, English Cocker Spaniel, Doberman, Fila Brasileiro, Lhasa Apso, German Shepherd and Malinois Shepherd. Furthermore, 15 dogs were of mixed breed. A 4-month-old male mixed-breed cat was diagnosed with a dermoid on the bulbar conjunctiva. It is possible to conclude that ocular dermoids most frequently affect young, mixed-breed dogs and Shih Tzus. They occur mainly unilaterally and especially affect the limbal regions of the cornea and the eyelids. Although rare, ocular dermoids can be diagnosed in cats.